Analysis of The Correlation Between Land Use Changes in Sub Watershed Wuno Toward Lifetime of Wuno Reservoir, Sigi District, Central Sulawesi Province - Wardani, Yuliana; Suhartanto, Ery; Haribowo, Riyanto (Fakultas Teknik UB, 2019)
Wuno Reservoir is located in Sigi Biromaru District, Sigi Regency, Central Sulawesi Province. It is planned for 50 years. This analysis to known the condition of ideal land use so that the life time of the reservoir reaches 50 years. Trend of land use change, erosion and sediment rate estimation using the ArcSWAT model. During 2008-2016, natural forest land use showed a downward trend, while mixed gardens, shrubs, fields and settlements showed an increasing trend. The erosion rate in 2008-2010 increased by 72.5%, in 2010-2012 it increased by 1.45%, in 2012-2014 decreased by 0.09% and in 2014-2016 increased by 0.98%. In 20082016 Low BEHI area was reduced by 3.74%, medium BEHI was increasing by 14.11%, BEHI High increased by 16.57% and BEHI Very High increased by 12.64%. This shows that the rate of erosion and the extent of BEHI are influenced by changes in land use. Based on the results of analyzing the lifetime of the reservoir, changes in land use also affect the reduced useful life of the reservoir. Vegetative land conservation efforts are adjusting forest areas so that rate of erosion decreases by 62.75%. Mechanical land conservation efforts in the form of the construction of 6 check dams so that weight of sediment decreases by 89.24%.